a). (x²+
) - (
+ 2x ) + (
-
) b). 2
-(
+
)+ (1
va roooggg
miladydanceclub:
trebuie sa simplifici?
Răspunsuri la întrebare
Răspuns de
1
(x²+x/3 ) - (x/3 + 2x ) + (5x²/6 -x/4 )=
=x²+x/3-x/3-2x+5x²/6-x/4=
=x²+5x²/6-2x-x/4=
=11x²/6-9x/4
b). 2 x/3-(4x²/5+2x/3)+ (1 2x²/3+0,(6)x-0,2x²=
=2+x/3-4x²/5+2x/3+ 1+ 2x²/3+2x/3-0,2x²=
=3+5x/3-4x²/5+ 2x²/3-x²/5=
=3+5x/3-x²+ 2x²/3=
=3+5x/3-x²/3
=x²+x/3-x/3-2x+5x²/6-x/4=
=x²+5x²/6-2x-x/4=
=11x²/6-9x/4
b). 2 x/3-(4x²/5+2x/3)+ (1 2x²/3+0,(6)x-0,2x²=
=2+x/3-4x²/5+2x/3+ 1+ 2x²/3+2x/3-0,2x²=
=3+5x/3-4x²/5+ 2x²/3-x²/5=
=3+5x/3-x²+ 2x²/3=
=3+5x/3-x²/3
Alte întrebări interesante
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Chimie,
10 ani în urmă